2018
DOI: 10.1097/scs.0000000000004083
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Precautions Before Sinus Lift Procedure

Abstract: The aim of the study was to evaluate the benefit of cone beam computed tomography (CBCT) and how to minimize injury to the posterior superior alveolar artery (PSAA) before sinus lift procedure. Cone beam computed tomography scans of 30 maxillary sinuses (15 patients) assessed to determine the location of PSAA presinus lift procedure. The data collected were used to extend the existed literature. The most common location of the PSAA was intraosseous (66.7%), the subantral distance mean was 5 ± 1 mm, and the mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…As regards the diameters, Bernardi et al [ 18 ], Danesh-Sani et al [ 26 ], Pandharbale et al [ 27 ], and Verela Centelles et al [ 28 ] found a mean diameter of 1.61, 1.17, 0.63, and 1.35 mm, respectively. In 2017, Al Ghurabi et al [ 29 ], Chitsazi et al [ 30 ], Lozano-Carrascal et al [ 31 ], Panjnoush et al, San Aung et al [ 32 ], and Tehranchi et al [ 33 ], found a frequency of 90%, 35%, 48.6%, 25%, 93%, and 87%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…As regards the diameters, Bernardi et al [ 18 ], Danesh-Sani et al [ 26 ], Pandharbale et al [ 27 ], and Verela Centelles et al [ 28 ] found a mean diameter of 1.61, 1.17, 0.63, and 1.35 mm, respectively. In 2017, Al Ghurabi et al [ 29 ], Chitsazi et al [ 30 ], Lozano-Carrascal et al [ 31 ], Panjnoush et al, San Aung et al [ 32 ], and Tehranchi et al [ 33 ], found a frequency of 90%, 35%, 48.6%, 25%, 93%, and 87%, respectively.…”
Section: Discussionmentioning
confidence: 99%